Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jcm9061605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthesia Techniques on Outcomes after Hip Fracture Surgery in Elderly Patients: A Prospective, Randomized, Controlled Trial

Abstract: The superiority of distinct anesthesia methods for geriatric hip fracture surgery remains unclear. We evaluated high mobility group box-1 (HMGB1) and interleukin-6 (IL-6) with three different anesthesia methods in elderly patients undergoing hip fracture surgery. Routine blood test findings, postoperative morbidity, and mortality were assessed as secondary outcome. In total, 176 patients were randomized into desflurane (n = 60), propofol (n = 58), or spinal groups (n = 58) that received desflurane-based balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…27,28 Furthermore, recent prospective studies have shown no significant association between the anesthesia method and the incidence of pneumonia or mortality in hip fracture surgery. 29,30 The results of the present study are consistent with the results of these recent reports. In the present study, the frequencies of atelectasis, pneumothorax, and pulmonary edema were very low, and there were no significant differences between the anesthesia groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…27,28 Furthermore, recent prospective studies have shown no significant association between the anesthesia method and the incidence of pneumonia or mortality in hip fracture surgery. 29,30 The results of the present study are consistent with the results of these recent reports. In the present study, the frequencies of atelectasis, pneumothorax, and pulmonary edema were very low, and there were no significant differences between the anesthesia groups.…”
Section: Discussionsupporting
confidence: 93%
“…The results of recent retrospective and prospective studies may support this third reason. [27][28][29][30] Fourth, many elderly patients with hip fractures are frail and suffer from cognitive impairment or chronic constipation. In frail patients, the muscles used to exhale vomit are presumed to be weak.…”
Section: Discussionmentioning
confidence: 99%
“…Male accounted for 50% or more of all patients in 4 trials ( 17 , 22 , 23 , 25 ). The mean or median age of all included patients was 80 years or older in five trials ( 20 , 26 , 31 33 ), 70–80 years in seven trials ( 21 , 28 , 29 , 34 37 ), 60–70 years in seven trials ( 17 , 18 , 23 25 , 27 , 30 ), and younger than 60 years in two trials ( 19 , 22 ). Except that the patients underwent lower limb vascular surgery in two articles ( 23 , 25 ) and uncertain surgeries in one article ( 19 ), the patients underwent orthopedic surgery in the other trials.…”
Section: Resultsmentioning
confidence: 99%
“…The patients in the RA group received the sole PNB in only two trials ( 17 , 29 ), and underwent PNB or neuraxial anesthesia in another two trials ( 25 , 35 ), while neuraxial anesthesia was the sole anesthesia in RA patients in the other 17 enrolled trials. The follow-up time was hospital stay after surgery in 13 trials ( 18 , 22 , 25 33 , 35 , 36 ), 1 year in one trial ( 23 ), 30 days in one trial ( 17 ), 1–7 days in one trial ( 20 ), 1–5 day in one trial ( 34 ), 1–4 days in one trial ( 37 ), 1–3 days in two trials ( 21 , 24 ), and 1 day in one trial ( 19 ). The methods of POD identification included antipsychotic drug use ( 17 , 18 , 22 , 30 ), Confusion Assessment Method for Intensive Care Unit (CAM-ICU) or CAM ( 19 , 21 , 36 , 37 ), DSM-IV criteria ( 24 , 27 ), NEECHAM confusion scale ( 25 ), change in mental state ( 23 ), and Pittsburgh Agitation Scale ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation